In Silico Design of Engineering Optimization via OptHandle for Effective Synthesis of Adipic Acid Precursor, α-Aminoadipate - Yang Zhang; Bingqi Cai; Meng Liu; Keqin He; Zhijin Gong; Haoran Bi; Kai Wang; Biqiang Chen; Meng Wang; Haijia Su; Tianwei Tan (Fermentation, 2023)
The green biosynthesis of adipic acid, an important monomer of nylon 6,6, has become a research hotspot. α-Aminoadipate is a key intermediate in the metabolic pathway that converts L-lysine to produce adipic acid. In addition, metabolic flux analysis has become an important part of metabolic engineering. Many metabolic optimization algorithms have been developed to predict engineering intervention strategies with the aim of improving the production of target chemicals. Here, OptHandle, a new metabolic optimization algorithm, has been developed. And, we use OptHandle to optimize the biosynthesis of α-aminoadipate. Based on the results of OptHandle, an engineered Escherichia coli with a 13-fold higher titer was obtained, and 1.10 ± 0.02 g/L of α-aminoadipate was produced. The efficient synthesis of α-aminoadipate lays a foundation for the green production of adipic acid.